2021
DOI: 10.1007/s13105-021-00837-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gut microbiota–derived extracellular vesicles on obesity and diabetes and their potential modulation through diet

Abstract: Obesity and diabetes incidence rates are increasing dramatically, reaching pandemic proportions. Therefore, there is an urgent need to unravel the mechanisms underlying their pathophysiology. Of particular interest is the close interconnection between gut microbiota dysbiosis and obesity and diabetes progression. Hence, microbiota manipulation through diet has been postulated as a promising therapeutic target. In this regard, secretion of gut microbiota–derived extracellular vesicles is gaining special attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 136 publications
(198 reference statements)
1
41
0
Order By: Relevance
“…Lv et al 10.3389/fcimb.2022.957439 In recent years, the geographic deviation among different subspecies has been described in several gut bacteria such as Prevotella copri (Tett et al, 2019) and Eubacterium rectale (Karcher et al, 2020). These findings suggested that not only the geographical factor but also other unknown factors (e.g., diet difference between populations (Cheng et al, 2021;Dıéz-Sainz et al, 2022), or movement of individuals) are probably the forces for speciation of the gut bacteria. Similarly, except for Amuc III, Amuc I, II, and IV were observed in the gut microbiota of American children in the study of Kirmiz et al (2020).…”
Section: Global Distribution Of Akkermansia Phylogroupsmentioning
confidence: 99%
“…Lv et al 10.3389/fcimb.2022.957439 In recent years, the geographic deviation among different subspecies has been described in several gut bacteria such as Prevotella copri (Tett et al, 2019) and Eubacterium rectale (Karcher et al, 2020). These findings suggested that not only the geographical factor but also other unknown factors (e.g., diet difference between populations (Cheng et al, 2021;Dıéz-Sainz et al, 2022), or movement of individuals) are probably the forces for speciation of the gut bacteria. Similarly, except for Amuc III, Amuc I, II, and IV were observed in the gut microbiota of American children in the study of Kirmiz et al (2020).…”
Section: Global Distribution Of Akkermansia Phylogroupsmentioning
confidence: 99%
“…Previous studies suggested that gut microbiota was associated with body weight ( Cuevas-Sierra et al., 2019 ), and obesity might be a risk factor for CCA progression and postoperative recurrence ( Merath et al., 2019 ; Zhou et al., 2020 ; Yugawa et al., 2021 ). There was evidence concerning the potential role of gut microbiota and probiotic-derived extracellular vesicles (EVs) on obesity via the modulation of inflammation, metabolism, and gut permeability ( Díez-Sainz et al., 2021 ). Although the clinical variables for CCA development were not included in our model, it was striking that genera Burkholderia-Caballeronia-Paraburkholderia were positively correlated with BMI, and biomarker genera had a higher abundance in individuals with BMI ≥23.01.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that gut microbiota participates in drug metabolism by producing specific enzymes, such as reductase and hydrolytic enzymes, thus affecting the efficacy, toxicity, and bioavailability of drugs. Various antibiotics also alter the diversity and composition of gut microbiota which leads to dysbiosis, and it was found to be linked with progression of various neurodegenerative as well as metabolic disorders [ 73 , 74 , 75 ].…”
Section: Diabetes and The Gut Microbiota: Dietary Influencementioning
confidence: 99%